A comparison of plasma electrolytic oxidation of Ti-6Al-4V and Zircaloy-2 alloys in a silicate-hexametaphosphate electrolyte. (20th May 2015) - Cheng, Yingliang; Peng, Zhaomei; Wu, Xiangquan; Cao, JinHui; Skeldon, P.; Thompson, G.E.
Graphical abstract: Highlights: PEO of Ti-6Al-4V and Zircaloy-2 is compared in the same electrolyte. More of the current consumed by oxygen evolution for theTi-6Al-4V alloy. Greater anomalous gas release after strong discharges for Zircaloy-2. "Coral reef" and pancake structures feature in the coatings on the respective alloys. Solid-state properties of coatings affect oxygen evolution and coating morphology. Abstract: Plasma electrolytic oxidation of Ti-6Al-4V and Zircaloy-2 alloys in a silicate-hexametaphosphate electrolyte has been studied in detail by various methods, including scanning electron microscopy, transmission electron microscopy and electrochemical techniques. Different coating growth kinetics, formation efficiencies and microstructures have been revealed for the two alloys. From these results, it is suggested that the insulating nature of the coating on Zircaloy-2 promotes the formation of pancake structures, which are formed by strong discharges. In contrast, the semiconducting properties of the coating on the Ti-6Al-4V alloy promote oxygen evolution, reduce the efficiency of coating growth and favour surface or shallow discharges that result in "coral reef" coating features. Anomalous gas evolution, which is more abundant with Zircaloy-2, was observed on both alloys after the appearance of stronger discharges. However, the current density used for the oxygen generation on Zircaloy-2 was still less than that of the Ti-6Al-4V alloy.